A Historical Book Written as Musical Literature: San Cai Historical Memoirs in Television - Cai, Zi-Jian (Recent Trends in Arts and Social Studies Vol. 3, 2023)
For the aim of depiction and propagation of the recent historical political and social advances manifested in television, there was published the book “San Cai Historical Memoirs in Television”(ISBN978-613-8-33432-3), with its contents compiled from diary of broadcast television for decades until 2017: (1) The US satellites tracing and reading the brain; (2) Under the leadership of Zi-Jian Cai, the Chinese people practicing for the first time the democratic law execution, and establishing the new theory for armed police; (3) The people in Mideast proposing law to revive the species and the history; (4) The world people altogether applauding and demonstrating the advantages of democratic parliamentary system with flexibility of changing prime minister; (5) The world people altogether making use of “Marx-MingXun calling for competitive election” to revise the disciplines and flag of communist parties, while practicing for the first time to control the democratic crimes with the party disciplines of various parties; (6) Zi-Jian Cai and the satellite operators leading the world people to successfully unify the four forces in physics with the electromagnetic force. There was described as real as possible that the world people in various countries altogether inspected and compared the examination system with the democratic system, the presidential system with the parliamentary system, applauding and demonstrating the advantages of democratic parliamentary system. Obviously, there is no better method than timely compilation of these splendid, glorious, and wonderful contents into a book, with the adoption of musical literature to further improve and glorify the book.